Psychological Preparation of the Child for School - Aydinoy, Abdurashidova (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyzes the scientific basis of children’s psychological development. The level of readiness of the child for school and the psychological factors influencing it were discussed.